Slow Stroke Back Massage and Lavender Aromatherapy to Improve Sleep Quality CKD Undergoing Hemodialysis - Tri Wahyuni; Febri Tri Ananda (GLOBAL HEALTH SCIENCE GROUP, 2024)
Chronic Kidney Disease (CKD) patients who undergo hemodialysis experience various complaints, one of which is sleep disturbances are the most complained symptoms by CKD patients undergoing hemodialysis. Proper therapy needs to be given to overcome the patient's sleep disorder problem. Aim: This study aims to explore the effect of the combination of Slow Stroke Back Massage (SSBM) and Lavender Aromatherapy on sleep quality in CKD patients undergoing hemodialysis. Methods: The sample in this study was 40 Hemodialysis Patients consisting of 20 intervention groups (treatment) and 20 control groups (standard treatment), sampling was carried out by non-prxobability sampling with purposive sampling technique. The research uses a quasi-experimental method with a pretest and post test conrol group design approach. Respondents will be given a pretest to assess their sleep quality, then respondents are divided into treatment groups given intervention and control groups not given intervention. The treatment group was given the intervention twice a week for four weeks. The next stage is to assess the posttest sleep quality of CKD patients in both the treatment group and the control group. The research data was obtained from guided interviews using the Pittburgh Sleep Quality Index (PSQI) questionnaire. Data analysis uses a comparative test from 2 measurement results in the same group, the data is normally distributed so that the Paired t-test is used.This study will outline the results of interventions carried out in the form of SSBM therapy and lavender aromatherapy with atomization technology in the form of diffusers in patients undergoing hemodialysis. Results: Based on the results of the study, it was found that SSBM therapy was significant in reducing sleep disorders in CKD patients undergoing hemodialysis with p=0.000 (p>0.05) while the control group was obtained p=0.09 (>0.05). Conclusion: SSBM therapy is expected to be applied as one of the interventions that can overcome sleep disorders in CKD patients undergoing hemodialysis.